A practical approach to preventing systematic error in the maintenance of instrumented safeguards. Issue 2 (9th November 2019) - Summers, Angela; Roche, Eloise
Abstract: Instrumentation and electrical (I&E) maintenance is typically managed using site‐wide policies, practices, and procedures. Since I&E equipment is part of the control system and nearly every other layer of protection, the cumulative impact of poor I&E performance can be a significant contributor to major events. Systematic problems in managing I&E equipment reliability lower process safety performance across a site. Practical guidance is needed on how to assess the vulnerability of existing sites to instrumented safeguard failure due to maintenance deficits. This paper leverages Reason's organizational accident model as a framework to discuss site‐specific factors that impact a site's susceptibility to maintenance error. A table of more than 60 human factors covering I&E maintenance activities was developed and organized by four elements of causality: organizational processes, workplace practices, personnel traits, and enabling conditions. The human factors table can be used to rate an industrial site on a negative‐to‐positive scale, highlighting those areas where systematic changes would likely improve maintenance performance and instrument reliability.